Групова класифікація квазілінійних рівнянь еліптичного типу II. Інваріантність відносно розв'язних алгебр Лі - Лагно, В.І.; Спічак, С.В. (Український математичний журнал, 2011)
Рассматривается задача групповой классификации квазилинейных уравнений эллиптического типа в двумерном пространстве. Получен перечень всех уравнений этого класса, допускающих разрешимые алгебры Ли операторов симметрии. Эти результаты вместе с результатами, полученными авторами ранее, дают исчерпывающее решение задачи групповой классификации квазилинейных уравнений эллиптического типа. The problem of the group classification of quasilinear elliptic-type equations in a two-dimensional space is considered. The list of all equations of this type, which admit the solvable Lie algebras of symmetry operators, is obtained. The results of this paper along with results obtained by the authors earlier give a complete solution of the problem of the group classification of quasilinear elliptic-type equations.